ANALISIS DETERMINAN OF NON PERFORMING LOAN (Studi pada Bank Umum BUMN di Indonesia) - Istiqomah, Nabilah; Buchori, Willa Putri Malinda; Nirbita, Betanika Nila (JURNAL CAPITAL : Kebijakan Ekonomi, Manajemen dan Akuntansi, 2024)
The purpose of this study is to determine: (1) the effect of LDR on NPL, (2) the effect of CAR on NPL, (3) the effect of Inflation on NPL, (4) the effect of BI rate on NPL at BUMN commercial banks for the period 2018-2023. This study is a casual associative research, quantitative approach. The population of this study, namely four BUMN commercial banks with a sample of four BUMN commercial banks and using purposive sampling technique. The research data used is secondary data in the form of quarterly financial reports for the 2018-2023 period of BUMN commercial banks. The data analysis technique used multiple linear regression with the help of the IBM SPSS 26 software program. The results showed that the positive effect of LDR on NPL with a beta value of 0.047 and a significance value of 0.000. Positive effect of CAR on NPL with beta value 0.064 and significance value 0.036. Inflation has no effect on NPL with a beta value of -0.056 and a significance value of 0.286. Negative effect of BI rate on NPL with beta value -0.487 and significance value 0.000. These findings indicate that banks need to be careful in managing LDR and CAR which have an influence on NPL. In addition, banks need to monitor macroeconomic factors such as inflation even though it has no effect, and BI rate can help reduce NPL.